Selected Lectures of the Course “Take care of children, 5th Edition. Inflammation between wellbeing and disease in Pediatrics” and the Meeting “Artificial intelligence in Medicine”; Cagliari (Italy); October 21, 2023 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2023)
Selected Lectures of the Course “Take care of children, 5th Edition. Inflammation between wellbeing and disease in Pediatrics” and the Meeting “Artificial intelligence in Medicine”; Cagliari (Italy); October 21, 2023 The Course “Take care of children, 5th Edition. Inflammation between wellbeing and disease in Pediatrics” and the Meeting “Artificial intelligence in Medicine” are Satellite Meetings of the 19th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 18th-21st, 2023. LECT 1. INFLAMMATION AND THE GUT • A. Staiano (Naples, Italy) LECT 2. UNDERSTANDING NEUROINFLAMMATION • D. Fanni (Cagliari, Italy) LECT 3. GUT DYSBIOSIS AND INFLAMMATION IN AUTISTIC SPECTRUM DISORDERS • M. Mussap (Cagliari, Italy) LECT 4. INFLAMMATION, NEUROINFLAMMATION AND IMMUNITY IN CHILDHOOD • O. Al Jamal (Cagliari, Italy) LECT 5. INFANT ATOPIC DERMATITIS AND NUTRITION: CAN LIPIDOMICS AND METABOLOMICS EXPLAIN THIS RELATIONSHIP? • A. Dessì, R. Pintus, A. Bosco, V. Fanos (Cagliari, Italy) LECT 6. PROBIOTICS AND PFAPA: RATIONALE FOR A PRECISION CHOICE • M. Matera (Grosseto, Italy) LECT 7. INFLAMMATION AND PREVENTION OF METABOLIC SYNDROME THROUGH NUTRACEUTICALS IN CHILDHOOD AND ADOLESCENCE • G. Trapani (Sanremo, Italy) LECT 8. REAL WORLD PRACTICE EXPERIENCES IN THE LOW DOSE APPROACH TO SPECIFIC LEARNING DISORDERS (ASDs). EVIDENCE FROM A RETROSPECTIVE OBSERVATIONAL STUDY • C. Supino (Itri, Italy) LECT 9. ANTI-MENINGOCOCCAL VACCINATION: THE IMPORTANCE OF THE BOOSTER IN ADOLESCENTS • P. Castiglia (Sassari, Italy) LECT 10. MICROBIOMICS IN CLINICAL PRACTICE • C. Marzetti (Bologna, Italy) LECT 11. ARTIFICIAL INTELLIGENCE IN MEDICINE • V. Fanos (Cagliari, Italy) LECT 12. ARTIFICIAL INTELLIGENCE IN MEDICINE: APPLICATION EXAMPLES • K.K. Kopeć (Cagliari, Italy) LECT 13. THE IMPERFECT BEAUTY • F. Velardi (Rome, Italy) LECT 14. ARTIFICIAL INTELLIGENCE: FROM POSTPARTUM DEPRESSION TO EXPOSOMICS • A. Colangelo (Trento, Italy)